Context and curriculum in two global cities: A study of discourses of citizenship in Hong Kong and Singapore - Theresa Alviar-Martin; Mark Baildon (Arizona State University, 2016)
This qualitative, comparative case study examined global civic education (GCE) in the Asian global cities of Hong Kong and Singapore. Guided by theories that position curriculum at the intersection of discourse, context, and personal meaning-making, we sought to describe the ways in which intentions for GCE reflect broader societal discourses of citizenship and how curricula allow students to tackle tensions surrounding national and global citizenship. We found that Singapore and Hong Kong have adopted depoliticized forms of citizenship as a means of inoculation against global ills. These types of citizenship are more nationalistic than global in nature; moral rather than political; and focused mainly on utilitarian goals to produce adaptable workers able to support national economic projects in the global economy. Although critical, transnational, and other emergent civic perspectives are apparent in both cities, the data yielded little evidence of curricular opportunities for students to become exposed to alternative discourses and reconcile discursive contradictions. The findings inform current literature by illuminating the nexus of local and global discursive practices, implicating the ability of curricula to accommodate both novel and established civic identities, and forwarding suggestions to bridge disconnections between theoretical and local curricular definitions of global citizenship.